An anti-CD19/CTLA-4 switch improves efficacy and selectivity of CAR T cells targeting CD80/86-upregulated DLBCL - Prinz, Lars Fabian; Riet, Tobias; Neureuther, Daniel Felix; Lennartz, Simon; Chrobok, Danuta; Hübbe, Hanna; Uhl, Gregor; Riet, Nicole; Hofmann, Petra; Hösel, Marianna; Simon, Adrian Georg; Tetenborg, Luis; et al. (Cell reports. Medicine, 2024)
Chimeric antigen receptor T cell (CAR T) therapy is a potent treatment for relapsed/refractory (r/r) B cell lymphomas but provides lasting remissions in only ∼40% of patients and is associated with serious adverse events. We identify an upregulation of CD80 and/or CD86 in tumor tissue of (r/r) diffuse large B cell lymphoma (DLBCL) patients treated with tisagenlecleucel. This finding leads to the development of the CAR/CCR (chimeric checkpoint receptor) design, which consists of a CD19-specific first-generation CAR co-expressed with a recombinant CTLA-4-linked receptor with a 4-1BB co-stimulatory domain. CAR/CCR T cells demonstrate superior efficacy in xenograft mouse models compared with CAR T cells, superior long-term activity, and superior selectivity in in vitro assays with non-malignant CD19+ cells. In addition, immunocompetent mice show an intact CD80−CD19+ B cell population after CAR/CCR T cell treatment. The results reveal the CAR/CCR design as a promising strategy for further translational study.